Muslim Americans: Debating the Notions of American and Un-American By Nahid Kabir (New York: Routledge, 2016. 307 pages.) (American Journal of Islam and Society, 2019)
Muslim Americans: Debating the Notions of American and Un-American is an ambitious attempt to explore how American Muslims, especially immigrants and their children, see the US and are seen by it. It uses the voices of Muslim Americans to explore what peoples and cultures can be considered American, and which are not. The author offers it as “a counter-narrative to the reactionary thinking of academics ... and some media and politicians who have place Islam/Muslims as the Other.”